Impaired butyrate absorption in the proximal colon, low serum butyrate and diminished central effects of butyrate on blood pressure in spontaneously hypertensive rats. (20th February 2019) - Yang, Tao; Magee, Kacy L.; Colon‐Perez, Luis M.; Larkin, Riley; Liao, Yan‐Shin; Balazic, Eliza; Cowart, Jonathan R.; Arocha, Rebeca; Redler, Ty; Febo, Marcelo; Vickroy, Thomas; Martyniuk, Christopher J.; et al.
Abstract: Aim: Butyrate is a major gut microbiota‐derived metabolite. Reduced butyrate‐producing bacteria has been reported in the spontaneously hypertensive rat (SHR), a model of hypertension characterized by dysfunctional autonomic nervous system and gut dysbiosis. Here, we demonstrate a potential mechanism for butyrate in blood pressure regulation. Methods: High‐performance liquid chromatography and liquid chromatography‐mass spectrometry were performed to measure butyrate levels in feces and serum. Ussing chamber determined butyrate transport in colon ex vivo. Real‐time PCR and immunohistochemistry evaluated expression of butyrate transporter, Slc5a8, in the colon. Mean arterial blood pressure was measured in catheterized anesthetized rats before and after a single butyrate intracerebroventricular injection. Activity of cardioregulatory brain regions was determined by functional magnetic resonance imaging to derive neural effects of butyrate. Results: In the SHR, we demonstrated elevated butyrate levels in cecal content, but diminished butyrate levels in circulation, possibly due to reduced expression of Slc5a8 transporter in the colon. In addition, we observed lower expression levels of butyrate‐sensing receptors in the hypothalamus of SHR, likely leading to the reduced effects of centrally administered butyrate on blood pressure in the SHR. Functional magnetic resonance imaging revealed reduced activation of cardioregulatory brain regions following central administration of butyrate in the SHR compared to control. Conclusion: We demonstrated a reduced availability of serum butyrate in the SHR, possibly due to diminished colonic absorption. Reduced expression of butyrate‐sensing receptors in the SHR hypothalamus may explain the reduced central responsiveness to butyrate, indicating microbial butyrate may play a role in blood pressure regulation.